From a Vision to Action: Implementing a Vison of Dialogue from Vatican II to Contemporary Catholic Schools Today - Joy, Benny Kaippullyparamban (Asian Horizons, 2025)
In the spirit of aggiornamento, the Second Vatican Council opened new avenues for the Catholic Church to engage in dialogue with the wider world. This path is notably outlined in documents such as Gaudium et Spes, Nostra Aetate, and Gravissimum Educationis. Among these, the latter (no. 25) specifically emphasises the vital role of Catholic schools in fulfilling the Church’s mission and fostering a mutually beneficial relationship between God’s people and humanity through dialogue. Extending this idea, the Congregation for Catholic Education issued its 2022 directive, The Identity of the Catholic School for a Culture of Dialogue, which expresses a clear preference for the so-called ‘Catholic dialogue school,’ yet lacks clarity regarding its kerygmatic or recontextualising forms. As society becomes increasingly diverse, the question arises whether this ‘kerygmatic’ form facilitates authentic interreligious learning in Catholic schools and meaningful dialogue with the religious ‘other’—people affiliated with different world views and religions. This paper begins with a brief analysis of the significance of ‘dialogue’ in Vatican II, presenting the context and respective approaches to the ‘Catholic dialogue school,’ particularly the recontextualising Catholic dialogue school (as a complementary or alternative model supported by a reinterpretation of the Church’s vision for dialogue). The paper further discusses the implications of shifting from a kerygmatic to a recontextualising Catholic dialogue school, highlighting the move from a correlational to a hermeneutical approach. Finally, it reflects on the implications and possibilities of this shift for Syro-Malabar Catholic schools in the Indian Keralite context.